DAMPAKPENCEMARANTIMBAL TERHADAP TUMBUH KEMBANG ANAK DIKOTA YOGYAKARTA TAHUN2000 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Abstract Y ogyakarta of populated and traditional city in Java due to the coming of student and tourists, and therefore there are many problems, for example the problem of living, traffic jam, public transportation, road safety, traffic accident including plumbom exposure to Yogyakarta's children.A cross-sectional research is done in Yogyakarta City center in the year 2000, and the research subject is chlidren who live in the populated area ofYogyakarta City Center. Measurements are conducted on the number of plumbom of the children drink water source (well water or pipeline water of government) and also the number of plumbom of the children urine, children psychomotoric development including their inteligent quotient (IQ). The result shows that 22,2% pof children drink water source contaminated by plumbom, children physical simptoms due to plumbom contamination are: 12% simptoms of leg and hand activities